The remarkably enhanced visible-light-photocatalytic activity of hydrothermally synthesized WO3 nanorods: An effect of Gd doping. Issue 3 (1st February 2021) - Govindaraj, T.; Mahendran, C.; Marnadu, R.; Shkir, Mohd; Manikandan, V.S.
Abstract: In this study, novel Gadolinium doped WO3 nanorods (Gd@WO3 NRs) were synthesized via facile hydrothermal method. The Gd@WO3 NRs were systematically characterized by XRD, RAMAN, FESEM, XPS, UV–Vis, and PL. XRD profiles confirmed the single phase of WO3, and the average crystallite size decreased with increasing the doping concentration. From EDS and XPS analysis of Gd@WO3 NRs, the presence of Gd, W, and O were confirmed without any additional peaks. UV–Vis spectra indicated that the position of the absorption edge lies within the visible region at all Gd contents in WO3, and the energy gap was studied. The photoluminescence test indicates that the 5 wt% of Gd doping in WO3 could reduce the photogenerated electron-hole pair recombination. The remarkable enhancement in the photodegradation activity for degrading the Rhodamine B under visible-light irradiation of WO3 was studied with Gd doping. The highest photocatalytic performance was found with 5 wt% Gd@WO3 NRs, due to the accelerated charge transfer process, which improved the photogenerated electron-hole pairs separation. According to trapping studies, the possible photocatalytic mechanism of Gd@WO3 NRs was also disclosed. The recycling test confirmed the stability of photocatalyst after three cycles. This novel Gd@WO3 NRs proved to be a superior catalyst for the reduction of organic pollutants.